2008
DOI: 10.1063/1.2963701
|View full text |Cite
|
Sign up to set email alerts
|

The absence of plasma in “spark plasma sintering”

Abstract: Spark plasma sintering (SPS) is a remarkable method for synthesizingand consolidating a large variety of both novel and traditional materials.The process typically uses moderate uni-axial pressures (< 100 MPa) in conjunction with a pulsing on-off DC current during operation. There are a number of mechanisms proposed to account for the enhanced sintering abilities of the SPS process. Of these mechanisms, the one most commonly put forth and the one that draws the most controversy involves the presence of momenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(76 citation statements)
references
References 17 publications
0
75
0
1
Order By: Relevance
“…The mechanism for densification in this process is the subject of some controversy. Early work by Tokita suggested that the densification occurred due to "sparks" forming between particles due to a plasma generated by the SPS apparatus [64], though later experimental work by Hulbert et al disputes this [65]. In many cases there is little difference between hot pressing (where heat is supplied by an induction furnace rather than electric current through the die) and spark plasma sintering [66], with the advantages of the later chiefly originating from superior heating rates and higher applied pressures [1].…”
Section: Comparison To Other Non-conventional Ceramic Firing Techniquesmentioning
confidence: 99%
“…The mechanism for densification in this process is the subject of some controversy. Early work by Tokita suggested that the densification occurred due to "sparks" forming between particles due to a plasma generated by the SPS apparatus [64], though later experimental work by Hulbert et al disputes this [65]. In many cases there is little difference between hot pressing (where heat is supplied by an induction furnace rather than electric current through the die) and spark plasma sintering [66], with the advantages of the later chiefly originating from superior heating rates and higher applied pressures [1].…”
Section: Comparison To Other Non-conventional Ceramic Firing Techniquesmentioning
confidence: 99%
“…Zhang et al proposed that the spark plasmas may play a key role to provide most of the energy required in this diamond transition, and it provided an indirect way to validate the existence of the plasmas during the SPS. Due to the still on-going arguments about whether the spark plasmas actually occur during the SPS process (Anselmi-Tamburini et al, 2005, Hulbert et al, 2008, it needs further investigations on this point. In this part, we used such an indirect way to prove the presence of plasmas during the SPS.…”
Section: Stability Of Carbon Nanotubes C60 and Graphite Under Varioumentioning
confidence: 99%
“…The name "Spark plasma sintering" is the most used denomination among a total of 60 found in the literature. [4] However, as no spark or plasma could be detected so far (which is a very difficult task anyway), [7,8] we prefer to add the more general name "field-assisted sintering technique," which also provides a convenient acronym. The common denomination "pulsed electric current sintering" insists upon the non-continuous nature of the electric supply.…”
Section: Definitionmentioning
confidence: 99%